Central Nervous System Injury Triggers Hepatic CC and CXC Chemokine Expression that Is Associated with Leukocyte Mobilization and Recruitment to Both the Central Nervous System and the Liver - Campbell, Sandra J. (2005)
The administration of interleukin-1beta to the brain induces hepatic CXC chemokine synthesis, which increases neutrophil levels in the blood, liver, and brain. We now show that such hepatic response is not restricted to the CXC chemokines. CCL-2, a CC chemokine, was released by the liver in response to a tumor necrosis factor (TNF)-alpha challenge to the brain and boosted monocyte levels. Furthermore, a clinically relevant compression injury to the spinal cord triggered hepatic chemokine expression of both types. After a spinal cord injury, elevated CCL-2 and CXCL-1 mRNA and protein were observed in the liver by TaqMan reverse transcriptase-polymerase chain reaction and enzyme-linked immunosorbent assay as early as 2 to 4 hours. Simultaneously, we observed elevated levels of these chemokines and circulating leukocyte populations in the blood. Leukocytes were recruited to the liver at this early stage, whereas at the site of challenge in the central nervous system, few were observed until 24 hours. Artificial elevation of blood CCL-2 triggered dose-dependent monocyte mobilization in the blood and enhanced monocyte recruitment to the brain after TNF-alpha challenge. Attenuation of hepatic CCL-2 production with corticosteroids resulted in reduced monocyte levels after the TNF-alpha challenge. Thus, combined production of CC and CXC hepatic chemokines appears to amplify the central nervous system response to injury.